Carbon monoxide methanation catalyst, producing method of carbon monoxide methanation catalyst, and method of reducing carbon monoxide in hydrogen-containing gas with the catalyst
The CO methanation catalyst on spherical porous silica with titanium oxide and ruthenium support addresses large-scale hydrogen production issues, ensuring low pressure loss and effective carbon monoxide conversion, thereby enhancing fuel cell longevity.
Patent Information
- Application Number
- JP2023109744
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-04
- Publication Date
- 2025-01-20
AI Technical Summary
Existing CO methanation catalysts are unsuitable for large-scale hydrogen production due to pressure loss and structural weakness, leading to reduced catalytic activity and potential adverse effects on subsequent stages.
A carbon monoxide methanation catalyst is developed using ruthenium supported on spherical porous silica with a thin film or island-like titanium oxide surface, formed by decomposing a water-soluble titanium complex, to create a strong structure that maintains catalytic activity and reduces pressure loss.
The catalyst effectively converts carbon monoxide to methane, reducing pressure loss and extending the lifespan of polymer electrolyte fuel cells by minimizing platinum catalyst poisoning.
Smart Images

Figure 2025007973000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a carbon monoxide methanation catalyst, a method for producing the carbon monoxide methanation catalyst, and a method for reducing carbon monoxide in a hydrogen-containing gas using the catalyst. [Background technology]
[0002] Hydrogen can be used to generate electricity by chemically reacting with oxygen using fuel cell technology, and can also be burned to generate thermal energy. Since the only substance produced by either reaction is water, hydrogen is attracting attention as a fuel source that does not emit carbon dioxide. Hydrogen is mainly produced by reforming, which extracts hydrogen from gas derived from fossil fuels or biomass through chemical reactions. These reformed gases contain carbon monoxide (CO) generated in the above chemical reaction process. This CO is reduced by a chemical reaction called the shift reaction, in which the gas reacts with water steam (CO+H2O→CO2+H2), allowing for further hydrogen production. After reforming, the CO ratio (volume basis) in the mixed gas obtained via this shift reaction is approximately 1%.
[0003] Currently, promising uses for hydrogen include fuel cell vehicles (FCVs), fuel cell buses (FC buses), and as fuel gas for the home fuel cell "ENE-FARM" (registered trademark). The solid polymer electrolyte fuel cells used as these batteries have a platinum catalyst in the electrode section, and if the fuel gas contains carbon monoxide, the platinum catalyst is poisoned and the cell efficiency decreases. Therefore, it is necessary to further reduce the CO in the gas obtained by the shift reaction, and it is required to keep it at 100 ppm or less, and more preferably 50 ppm or less. Therefore, a method of removing carbon monoxide from a hydrogen-containing gas by methanation has been investigated.
[0004] Patent Document 1 describes a catalyst for methanating carbon monoxide (hereinafter referred to as a "CO methanation catalyst") having a titanium content of 1 to 49 mass %, an average pore diameter of 1 to 10 nm, and a pore size of 400 to 2000 m. 2 The document describes a catalyst in which ruthenium is supported in the pores of a porous silica material having a specific surface area of 1.0 nm / g and at least one peak at a position where the d-spacing of X-ray diffraction is greater than 2.0 nm.
[0005] Patent Document 2 describes a CO methanation catalyst in which ruthenium having a particle size of 10 nm or less is attached to at least one type of support selected from zirconia, alumina, titania, and silica. It describes that the particle size of the support is usually 5 to 20 μm, preferably 10 μm, and that the particle size of the aggregated support is usually 1 to 5 mm, preferably 3 mm.
[0006] Patent Document 3 describes an inorganic composite of titanium oxide and an inorganic compound obtained by combining a titanium compound having a cyclic structure in which two or more titanium atoms are alternately bonded to oxygen atoms with an inorganic compound as a catalyst for converting propylene to propylene oxide by a gas-phase oxidation reaction, and then decomposing the titanium compound. In addition, the titanium compound described above includes titanium ammonium peroxocitrate or a derivative thereof. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2012-250143 A [Patent Document 2] JP 2005-67917 A [Patent Document 3] JP 2005-193226 A Summary of the Invention [Problem to be solved by the invention]
[0008] In order to promote the use of hydrogen, it is necessary to reduce the cost of hydrogen production, and there is a demand for expanding the scale of production and making the process continuous. To achieve large-scale production, it is necessary to reduce pressure loss (hereinafter referred to as "pressure loss") so that hydrogen-containing gas can flow smoothly inside a large reaction tube. However, for example, the CO methanation catalysts described in Patent Documents 1 and 2 are powders with pore sizes, specific surface areas, or particle sizes suitable for small-scale laboratory-scale experiments, and if used as is in a large reaction tube, excessive pressure loss will occur. In addition, there is a concern that the outflow of the powder may have a negative impact on subsequent stages.
[0009] In order to reduce pressure loss, it is possible to mold the powder with a press or the like to increase the particle size. However, it is difficult to mold the powder catalyst into a molded body with sufficient strength, and the catalyst collapses and re-pulverizes during gas flow, making it impossible to sufficiently reduce pressure loss. In addition, if moldability is increased by applying excessive pressure, the reaction area between the catalytic active components and the gas is narrowed, and sufficient catalytic activity cannot be obtained. In view of the above-mentioned problems, the present invention aims to provide a robust CO methanation catalyst that can reduce pressure loss of a hydrogen-containing gas even when packed into a large reaction tube and is less likely to have an adverse effect on downstream stages, and a method for producing the same, as well as to provide a method for efficiently converting carbon monoxide in a hydrogen-containing gas into methane to reduce carbon monoxide. [Means for solving the problem]
[0010] The present inventors have conducted various investigations into a robust CO methanation catalyst that enables a large-scale system for reducing carbon monoxide from a hydrogen-containing gas to be enlarged, and have arrived at the present invention. That is, in order to solve the above problems, the present invention employs the following means.
[0011] (1) A carbon monoxide methanation catalyst comprising ruthenium supported on spherical porous silica having a particle size of 1.0 mm or more and having a thin film or island-like titanium oxide on its surface. (2) The carbon monoxide methanation catalyst according to (1) above, wherein the titanium oxide has a cyclic structure in which two or more titanium atoms are alternately bonded to oxygen atoms. (3) The carbon monoxide methanation catalyst according to (1) or (2), wherein the spherical porous silica has an average pore diameter of more than 10 nm. (4) The specific surface area of the spherical porous silica is 200 m 2 The carbon monoxide methanation catalyst according to any one of (1) to (3), wherein the carbon monoxide methanation catalyst has a molecular weight of 1000 to 15000 kcal / g or less. (5) Adding a water-soluble titanium complex to spherical porous silica having a particle size of 1.0 mm or more; forming a thin film or islands of titanium oxide on the surface of the spherical porous silica by decomposition of the titanium complex; Supporting ruthenium on the spherical porous silica. A method for producing a carbon monoxide methanation catalyst. (6) The method for producing a carbon monoxide methanation catalyst according to (5) above, wherein the water-soluble titanium complex is titanium ammonium peroxocitrate or a derivative thereof. (7) The method for producing a carbon monoxide methanation catalyst according to (5) or (6) above, wherein the titanium oxide has a cyclic structure in which two or more titanium atoms are alternately bonded to oxygen atoms. (8) A method for producing the carbon monoxide methanation catalyst according to any one of (5) to (7) above, comprising supporting ruthenium on the spherical porous silica using a hexaammineruthenium complex as a ruthenium precursor. (9) A method for reducing carbon monoxide contained in a hydrogen-containing gas by converting carbon monoxide into methane using any one of the carbon monoxide methanation catalysts (1) to (4) above. Effect of the Invention
[0012] The CO methanation catalyst and the method for producing a CO methanation catalyst according to the present invention can provide a robust catalyst that can reduce pressure loss of a hydrogen-containing gas and does not affect downstream stages, even when packed into a reaction tube of a large-scale device. Furthermore, the method for reducing carbon monoxide of the present invention converts carbon monoxide into methane and removes it from hydrogen-containing gas, reducing poisoning of the platinum catalyst in a polymer electrolyte fuel cell and extending the life of the fuel cell. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 shows the effect of the presence or absence of titanium treatment on the carbon monoxide reduction effect of the catalyst carrier of the present invention. [Diagram 2] FIG. 1 shows the effect of changing the reaction scale in the catalyst of the present invention on the carbon monoxide reduction effect. [Diagram 3] FIG. 1 shows the stability of carbon monoxide reduction effect over time in the present invention. [Figure 4] FIG. 1 is a diagram showing the effect of the amount of titanium complex used in the catalyst of the present invention on the carbon monoxide reduction effect. [Diagram 5] FIG. 1 shows the effect of ruthenium precursors in the catalysts of the present invention on carbon monoxide reduction. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The present invention provides a carbon monoxide methanation catalyst comprising ruthenium supported on spherical porous silica having a particle size of 1.0 mm or more and having thin film or island-like titanium oxide on the surface and / or in the pores, and a method for producing the catalyst, the method comprising: adding a water-soluble titanium complex to spherical porous silica having a particle size of 1.0 mm or more, heating and calcining the silica to form thin film-like or island-like titanium oxide on the surface and / or in the pores of the spherical porous silica, and contacting the spherical porous silica with ruthenium chloride or a hexaammineruthenium complex, heating and calcining the silica to support ruthenium on the spherical porous silica. The present invention also provides a method for reducing carbon monoxide contained in a hydrogen-containing gas by converting carbon monoxide into methane using the above catalyst.
[0015] Hereinafter, the CO methanation catalyst, the method for producing the CO methanation catalyst, and the method for reducing carbon monoxide contained in a hydrogen-containing gas according to an embodiment of the present invention (hereinafter referred to as "the present embodiment") will be described in detail in this order. In addition, when a numerical range is expressed using "~", it means that the numerical values stated as the lower limit and upper limit are also included.
[0016] [Spherical porous silica] The spherical porous silica according to this embodiment is bead-shaped (spherical) silica having a particle diameter of 1.0 mm or more. Note that particles having a particle diameter of 1.0 mm or more refer to an aggregate of particles that do not pass through a sieve with an opening of 1.0 mm (16 mesh). The beaded silica may be a commercially available product, and examples of the products that can be used include those with a particle size of 1.7 mm or more, such as CALiACT (registered trademark) series Q-15, Q-30, and Q-50 manufactured by Fuji Silysia Chemical Ltd. This beaded silica is a strong spherical molded body, and has the following physical properties (catalog values):
[0017] [Table 1]
[0018] The following simulation results show that when spherical carriers with a particle size of 1.0 mm or more are used, there is almost no effect of pressure loss. To calculate the pressure drop ΔP, the widely known Ergun formula shown below is used.
[0019]
number
[0020] Assuming a practical scale shift reaction, the flow rate of the gas to be treated is 13 NL / min, and 300 g of spherical catalyst is used. This catalyst is packed into three types of tubes with diameters of 20 mm, 30 mm, and 40 mm. Assuming that the amount of catalyst is kept constant at 300 g, the length (L) of the catalyst packing section changes depending on the tube diameter. The assumed parameters are as follows: Viscosity of process gas μ=5×10 -5 Pa·s Density of treated gas ρ=1kg / m 3 Catalyst packing part void ratio ε=0.4 Catalyst particle diameter D p =1.0mm When these conditions were set, the calculated pressure loss ΔP was 35.2 kPa when the pipe diameter was 20 mm, 6.1 kPa when it was 30 mm, and 1.9 kPa when it was 40 mm. Assuming that the catalyst particle diameter is 1.0 mm, as described above, in this calculation, the pressure drop ΔP is a low value that has almost no practical effect. If the catalyst particle diameter is more than 1.0 mm, the value is even lower. Therefore, it can be said that the CO methanation catalyst using the spherical porous silica according to this embodiment is hardly affected by pressure drop. Similarly, if the catalyst packing void ratio ε is assumed to be 0.4, the pressure drop ΔP in this calculation will be a low value that does not require consideration of practical effects, as described above. If the catalyst packing void ratio ε is more than 0.4, the value will be even lower. The void ratio ε of the catalyst packed part is calculated by dividing the true density ρ A (The mass per unit volume of the particle measured without any voids or cracks in the particle) and the bulk density ρ B (The powder mass per unit bulk volume is calculated by dividing the powder mass by the bulk volume it occupies) and using ε=1-ρ B / ρ A It is required as follows. The bulk density ρ of the catalyst when packed depends on the number of tappings and the shape of the catalyst particles. Bchanges, so ε also changes. However, for example, the preferred bulk density for a silica carrier is 0.3 to 0.7 g / cm 3 (See Japanese Patent No. 6910252, paragraph
[0037] .) The true density of spherical silica is 1.8 g / cm 3 (https: / / www.silicone.jp / products / notice / spherical_silica / index.shtml), 2.2g / cm 3 (http: / / www.toyotakako.com / silicagel.html), it can be said that the void ratio ε of the catalyst packed part will not fall below 0.4.
[0021] The spherical porous silica according to this embodiment may have an average pore diameter of more than 10 nm. The average pore diameter of the conventional CO methanation catalyst carrier is preferably 10 nm or less in order to highly disperse and support the catalytically active component and maintain the catalytic activity. However, in the present embodiment, the titanium oxide having the titanium polynuclear structure shown in the next section is formed on the surface of the spherical porous silica, so that the catalytic activity is significantly improved, and it is possible to maintain the catalytic activity and improve the diffusibility of the gas even when a carrier with a larger average pore diameter is used. The average pore diameter of the spherical porous silica is preferably more than 10 and 100 nm or less, more preferably 15 to 50 nm.
[0022] In addition, the specific surface area of the spherical porous silica according to this embodiment may be smaller than the specific surface area of a conventional CO methanation catalyst. The specific surface area of a conventional CO methanation catalyst is 400 m2 in order to highly disperse the catalytically active components and maintain catalytic activity. 2 / g or more is preferable. However, in this embodiment, the titanium oxide having a titanium polynuclear structure shown in the next section is formed on the surface of the spherical porous silica, so that the catalytic activity is significantly improved, and therefore, even if a carrier with a smaller specific surface area is used, the catalytic activity can be maintained and the gas diffusibility can be improved. The specific surface area of the spherical porous silica is 200 m 2 / g or less, and2 It is more preferable that the molecular weight is not more than 1 / g. By having the above average pore size and specific surface area, the catalyst particles according to this embodiment can be made strong.
[0023] [Titanium oxide] The titanium oxide according to this embodiment is formed in a thin film or island shape on the surface of the spherical porous silica. The titanium oxide is preferably a titanium oxide having a cyclic structure in which two or more titanium atoms are alternately bonded to oxygen atoms (hereinafter referred to as a "titanium polynuclear structure"). The titanium oxide having a titanium polynuclear structure can be prepared by using a titanium compound having a unique local structure having a cyclic structure in which two or more titanium atoms are alternately bonded to oxygen atoms as a precursor. In particular, a titanium complex having a four-membered ring structure shown in the following Chemical formula 1 or 2 as a structural unit is preferably used as the titanium oxide precursor.
[0024] [ka] In the above formula, oxygen is bonded to A, B, C, and D, and each oxygen has a bond to another Ti atom or Si atom not shown in the above formula in addition to the bond to Ti shown in the above formula.
[0025] [ka] In the above formula, oxygen is bonded to A, B, C, D, E, F, G, and H, and each oxygen has a bond to another Ti atom or Si atom not shown in the above formula in addition to the bond to Ti shown in the above formula.
[0026] The titanium oxide having a titanium polynuclear structure is preferably a decomposition product of a water-soluble titanium complex having a titanium polynuclear structure, and is preferably a decomposition product of ammonium titanium peroxocitrate (chemical formula: (NH4)4[Ti2(C6H4O7)2(O2)2] or (NH4)8[Ti4(C6H4O7)4(O2)4]) or a derivative thereof.
[0027] The titanium oxide having a titanium polynuclear structure according to this embodiment strongly bonds titanium atoms to the surface of the spherical porous silica, thereby improving the activity of the support surface and improving the catalytic activity of ruthenium.
[0028] [ruthenium] The ruthenium in this embodiment is a catalytically active component supported on a support having titanium oxide formed on the surface (hereinafter referred to as a "titanium-treated support"), and catalyzes the reaction in which carbon monoxide is reduced with hydrogen to form methanation. In particular, it is used to remove carbon monoxide from a reformed gas that is mainly composed of hydrogen and contains a small amount of carbon monoxide.
[0029] [Method of manufacturing CO methanation catalyst] The method for producing a CO methanation catalyst according to this embodiment includes the steps of adding a water-soluble titanium complex as a titanium oxide precursor to spherical porous silica, and decomposing the precursor to form a thin film or island-like titanium oxide on the surface of the spherical porous silica (hereinafter referred to as "titanium treatment"). Then, ruthenium is supported on the spherical porous silica on which the titanium oxide has been formed.
[0030] The water-soluble titanium complex (titanium oxide precursor) is preferably titanium ammonium peroxocitrate (chemical formula: (NH4)4[Ti2(C6H4O7)2(O2)2] or (NH4)8[Ti4(C6H4O7)4(O2)4]) or a derivative thereof. This titanium oxide precursor has a cyclic structure in which two titanium atoms are alternately bonded to an oxygen atom (titanium polynuclear structure).
[0031] This titanium oxide precursor is decomposed by applying external energy such as heat, electromagnetic waves, or radiation, and a thin film or islands of titanium oxide are formed on the surface of the spherical porous silica. When the external energy is heat, the temperature is preferably 300 to 700° C., more preferably 400 to 600° C., and the heating time is preferably 1 to 24 hours, more preferably 2 to 12 hours. By applying the preferred external energy, the decomposition of the titanium oxide precursor is promoted, and a support is obtained in which titanium oxide having a thin film-like or island-like titanium polynuclear structure is firmly bonded to the surface of the spherical porous silica.
[0032] The amount of titanium oxide precursor added is preferably 5 to 40 parts by mass relative to 100 parts by mass of spherical porous silica. In order to improve the CO methanation catalytic activity and CO reaction selectivity, it is more preferably 10 parts by mass or more. In order to support ruthenium in a highly dispersed manner and maintain catalytic activity while maintaining the specific surface area and pore volume of the spherical porous silica, it is more preferably 30 parts by mass or less.
[0033] The CO methanation catalyst according to this embodiment is produced by supporting ruthenium, which is a catalytically active component, on the spherical porous silica on which the titanium oxide is formed. For example, ruthenium can be supported by impregnating the support on which the titanium oxide is formed with an aqueous solution of a ruthenium precursor, and then heating and calcining the same. The ruthenium precursor is preferably a hexaammineruthenium complex, since a small amount of the complex can achieve a carbon monoxide removal rate of 100% at a reaction temperature of 200° C., but from the perspective of cost, ruthenium chloride may also be used.
[0034] [CO reduction methods] The CO reduction method according to this embodiment is a method for converting carbon monoxide contained in a hydrogen-containing gas into methane and reducing the amount of carbon monoxide by using a CO methanation catalyst in which ruthenium, a catalytically active component, is supported on the spherical porous silica having titanium oxide on its surface. Currently, hydrogen-containing gas is generally obtained by reforming gas derived from fossil fuels or biomass, and even if the reforming reaction is followed by a shift reaction in which the gas is reacted with steam, the gas still contains approximately 1% carbon monoxide and approximately 20% carbon dioxide as a standard. If such reformed gas is used as fuel gas, for example, the platinum catalyst contained in the electrodes of a polymer electrolyte fuel cell will be poisoned by CO, shortening the life of the electrodes in the cell, which is undesirable.
[0035] The carbon monoxide reduction method according to this embodiment can be applied to the reduction of carbon monoxide in the reformed gas as described above. In particular, by applying the carbon monoxide reduction method according to this embodiment to the reforming of hydrogen-containing gas supplied to a polymer electrolyte fuel cell, it is possible to reduce poisoning of the platinum catalyst used in the electrodes and extend the life of the fuel cell. EXAMPLES
[0036] The present invention will be specifically described below based on examples and comparative examples. It should be noted that the examples are merely preferred examples of the present invention, and the present invention is not limited to the following examples.
[0037] (Production Example 1: Production of titanium-treated carrier) (1) Titanium treatment As spherical porous silica, CARiACT (registered trademark) series Q-50 (physical properties: specific surface area: 80 m 2 To 20 g of silica beads (average pore size: 1.0 mL / g, pore volume: 1.0 mL / g, average pore size: 50 nm, particle size: 1.7 to 4.0 mm), an aqueous solution of 12.0 g of titanium peroxocitrate ammonium (TAS-FINE Ti20% powder manufactured by Furuuchi Chemical Co., Ltd.) was added as a water-soluble titanium complex, which is a titanium oxide precursor. The amount of titanium oxide precursor added corresponds to 20 g of titanium oxide (assuming that the average structure is TiO2) formed after heating and baking per 100 g of silica beads, and this ratio is expressed as "20%". The same notation is used below. The aqueous solution containing the silica beads and the titanium oxide precursor was kept at 60°C for 5 hours. The temperature was then raised to 80°C and heated overnight to evaporate the water and dry the mixture, obtaining silica beads impregnated with the titanium oxide precursor. The silica beads were inserted into a heating furnace in air, and after the furnace temperature reached 500°C, they were heated and fired for 3 hours to obtain a silica bead support having thin-film or island-like titanium oxide on its surface. Hereinafter, the silica bead support obtained by this titanium treatment is referred to as a "Ti-containing silica bead support."
[0038] (2) Ruthenium loading To 20 g of Ti-containing silica bead carrier, an aqueous solution containing 0.41 g of hexaammineruthenium complex (hexaammineruthenium (III) chloride) as a ruthenium precursor was added. The amount of this ruthenium precursor added was equivalent to 1 g of Ru metal per 100 g of Ti-containing silica bead carrier, and this ratio is expressed as "1%". The same notation is used below. The aqueous solution containing the Ti-containing silica bead carrier and the ruthenium precursor was kept at 60°C for 5 hours. The temperature was then raised to 80°C and heated overnight to evaporate the water. The mixture was heated and calcined in air at 500°C for 3 hours (the time from when the heating furnace reached 500°C) to obtain catalyst particles in which 1% of ruthenium was supported on the Ti-containing silica bead carrier in terms of metal (hereinafter referred to as "Ru / TiO2-SiO2 catalyst particles A"). In addition, a 1% aqueous solution of ruthenium (III) nitrosyl nitrate (Ru(NO)(NO3)) was used as the ruthenium precursor. x (OH) y , x+y=3: hereinafter referred to as "Ru-NNN.") was used, and the same procedure as in the above production example was repeated to obtain "Ru / TiO2-SiO2 catalyst particles B" with a Ru metal loading of 1%. Furthermore, "Ru / TiO2-SiO2 catalyst particle C" with a Ru metal loading of 1% and "Ru / TiO2-SiO2 catalyst particle D" with a Ru metal loading of 2% were obtained in the same manner as in the above production example, except that 1% or 2% of ruthenium chloride (RuCl3) was used as the ruthenium precursor.
[0039] (Production Example 2: Production of a carrier without titanium treatment) Ruthenium-loaded catalyst particles were obtained using 1% hexaammineruthenium complex as a ruthenium precursor on a silica bead support that did not contain titanium and was not treated with titanium.
[0040] Example 1: Use of titanium-treated support 1.0 g of Ru / TiO2-SiO2 catalyst particles A obtained in Production Example 1 was packed into a Pyrex (registered trademark) glass reaction tube having an outer diameter of 16 mm and an inner diameter of 12.8 mm. Quartz wool was packed at the outlet side to prevent the catalyst from flowing away. A mixed gas containing 74% hydrogen, 20% carbon dioxide, 1% carbon monoxide, and 5% nitrogen as an internal standard gas was prepared as a simulated gas for a fuel cell (the same simulated gas was used in all of the following examples and comparative examples). The mixed gas was filled into a gas cylinder, and a water vapor gas generator capable of vaporizing liquid water kept at 130 to 140°C was connected to a gas line piping from the gas cylinder through a pressure regulating valve. Water (19 mL / min in terms of water vapor) was circulated through the water vapor gas generator at a pump setting of 15 μL / min, and the generated water vapor was added to and mixed with the mixed gas at a flow rate of 50 mL / min (by a gas flow rate regulator), while the set temperature of the external heating electric furnace was set to 200°C and the gas was circulated through a reaction tube. The moisture content relative to the gas flow rate is set to be kept at a constant condition. The degree of reduction in carbon monoxide in the gas exhausted from the reaction tube was evaluated by gas chromatography using a thermal conductivity detector (TCD-GC, GC-14B model, manufactured by Shimadzu Corporation) with nitrogen as the internal standard, which does not increase or decrease due to catalytic reactions. The degree of reduction in carbon monoxide was also evaluated when the set temperature was changed to 170°C, 180°C, 190°C, and 220°C.
[0041] (Comparative Example 1: Use of a carrier not treated with titanium) A catalytic reaction was carried out under the same conditions as in Example 1 using the catalyst particles obtained in Production Example 2. FIG. 1 shows the evaluation results of the degree of reduction in carbon monoxide in Example 1 and Comparative Example 1.
[0042] From Figure 1, it can be seen that when Ru / TiO2-SiO2 catalyst particle A is used, it is possible to remove 100% of carbon monoxide at a reaction temperature of 200°C, whereas when a catalyst that is not titanium-treated is used, the carbon monoxide reduction rate is less than 30% even at a reaction temperature of 200°C, and does not reach 40% even at 220°C, where the reaction activity should be even higher. Therefore, it is clear that the CO methanation catalyst of the present invention requires titanium treatment.
[0043] Example 2: Varying the reaction scale Using 4.0 g of Ru / TiO2-SiO2 catalyst particles A obtained in Production Example 1, a catalytic reaction was carried out in the same manner as in Example 1, except that the water flowing through the reaction tube was 60 μL / min (75 mL / min in terms of water vapor) and the flow rate of the simulated gas was 200 mL / min, making the reaction scale four times larger, and the carbon monoxide reduction rate was evaluated. The results are shown in Figure 2.
[0044] FIG. 2 confirms that, even when the reaction scale is increased, when titanium-treated catalyst particles are used, 100% of carbon monoxide can be removed at a reaction temperature of 200°C.
[0045] (Example 3: Confirmation of stability over time) Using 4.0 g of Ru / TiO2-SiO2 catalyst particles A obtained in Production Example 1, a catalytic reaction was carried out at a reaction temperature of 200°C on the same scale as in Example 2 (flow rate of simulated gas: 200 mL / min, flow rate of water: 60 μL / min), and the reduction in carbon monoxide in the gas exhausted from the reaction tube was evaluated 3 to 111 minutes (at 12-minute intervals) after the start of the reaction. The evaluation results are shown in Figure 3.
[0046] Figure 3 shows that the CO methanation catalytic reaction occurs stably for a long period of time, even when the reaction scale is large.
[0047] (Example 4: Consideration of titanium processing amount) A catalytic reaction was carried out on catalyst particles obtained in the same manner as in Production Example 1, except that the ratio of titanium ammonium peroxocitrate added to the silica beads was changed from 20% to 10% and 40%, at a reaction temperature of 170 to 220°C and on the same reaction scale as in Example 2 (flow rate of simulated gas: 200 mL / min), and the degree of reduction in carbon monoxide was evaluated. The evaluation results are shown in Figure 4. In the figure, "TiO2complex" represents titanium ammonium peroxocitrate.
[0048] 4 shows that in the CO methanation catalyst of the present invention, when the amount of the titanium complex used is 10% or 20%, 100% of carbon monoxide can be removed at a reaction temperature of 200° C. On the other hand, when the amount of the titanium complex used is 40%, 100% of carbon monoxide was not removed at a reaction temperature of 200° C. Therefore, it is found that the amount of titanium complex used is sufficient if it is 10% or more, and it is preferable that it does not exceed 40%.
[0049] (Example 5: Study of ruthenium precursor) The Ru / TiO2-SiO2 catalyst particles A (hexaammineruthenium complex with 1% ruthenium precursor) obtained in Production Example 1, Ru / TiO2-SiO2 catalyst particles B (Ru-NNN with 1% ruthenium precursor), Ru / TiO2-SiO2 catalyst particles C (RuCl3 with 1% ruthenium precursor), and Ru / TiO2-SiO2 catalyst particles (RuCl3 with 2% ruthenium precursor) were filled into a reaction tube, the reaction temperature was set to 170 to 220 ° C, and a catalytic reaction was performed at the same reaction scale as in Example 2 (flow rate of simulated gas: 200 mL / min), and the reduction degree of carbon monoxide was evaluated. Figure 5 shows the evaluation results by changing the ruthenium precursor.
[0050] From FIG. 5, it can be seen that Ru / TiO2-SiO2 catalyst particle B using Rn-NNN as a ruthenium precursor and Ru / TiO2-SiO2 catalyst particle C using ruthenium chloride to produce Ti-containing catalyst particles carrying 1% Ru in metal equivalent are ineffective for carbon monoxide reduction unless the reaction temperature is 220°C. In contrast, Ru / TiO2-SiO2 catalyst particle A using hexaammineruthenium complex as a ruthenium precursor achieves 100% carbon monoxide reduction at a reaction temperature of 200°C. Therefore, in order to carry 1% Ru metal on Ti-containing catalyst particles and remove carbon monoxide at a reaction temperature of 200°C, it is preferable to use a hexaammineruthenium complex. However, Ru / TiO2-SiO2 catalyst particles D, which use 2% ruthenium chloride as a precursor and support 2% Ru in metal equivalent, can reduce carbon monoxide by 100% at 200° C. Therefore, taking into consideration the cost of reagents, etc., it can be said that it is practical to manufacture Ru / TiO2-SiO2 catalyst particles using 2% ruthenium chloride in metal ruthenium equivalent as a ruthenium precursor.
[0051] Example 6: Precision measurement of carbon monoxide reduction The thermal conductivity detector gas chromatography (TCD-GC) used in the above examples is known to have a somewhat high detection limit concentration. In the above examples, in order to precisely analyze and confirm whether carbon monoxide had been sufficiently reduced to a concentration (less than 50 ppm) that would not adversely affect the electrodes of the polymer electrolyte fuel cell, an experiment was conducted to more accurately investigate the carbon monoxide concentration after reduction using a precision CO meter (CGT-7100 model) manufactured by Shimadzu Corporation. The catalyst particles used were 5 g of Ru / TiO2-SiO2 catalyst particles A obtained in Production Example 1. These were packed into a bulge-type glass reaction tube, and a simulated gas was passed through at the reaction temperature and flow rate shown in Table 2 below to carry out a catalytic reaction.
[0052] [Table 2]
[0053] Under conditions where 100% carbon monoxide reduction has not been achieved with the TCD-GC, the values are outside the range of the CO precision measuring instrument, so the CO measurement values No. 1 and 2 measured by the CO precision measuring instrument are not listed. With TCD-GC, the conversion rate is 100% (residual CO concentration is below the detection limit) at reaction temperatures of 200°C or higher, so the residual CO was analyzed using the above precision measuring device under conditions of 100% conversion rate measured by TCD-GC. As a result, the residual CO concentration was achieved at a maximum of 29.8 ppm, less than 50 ppm, in all temperature ranges above 200°C, and at a higher reaction temperature of 205°C, a maximum of 16.0 ppm was obtained. This analysis showed that the CO reduction effect (catalytic performance) of the simulated gas through the methanation reaction had reached a practically usable level.
[0054] (Example 7: Study of the ratio of catalyst usage amount and gas flow rate) Next, in order to clarify the appropriate ratio between the amount of catalyst used and the gas flow rate, an experiment was carried out in which the amount of catalyst used was fixed at 5 g, the reaction temperature was set at 205°C, and the flow rate of the simulated gas was changed. The conditions and results are shown in Table 3 below.
[0055] [Table 3]
[0056] From Table 3, it becomes clear that the limit of the throughput per gram of catalyst (corresponding to simulated gas with a 1% CO content) is about 55 mL / min. In addition, CO2 quantitative analysis was also performed by TCD-CG under the conditions listed in Table 3. When the CO conversion rate was 100%, no reduction in CO2 caused by the reaction of CO2 and hydrogen was confirmed, so it was verified that CO2 was hardly converted to CO at reaction temperatures of around 205 to 210°C, and that it was possible to remove CO from the simulated gas. This result indicates that hydrogen, which is the fuel for the fuel cell, is hardly consumed in the methanation of CO2, which is an unnecessary reaction other than CO methanation. [Industrial Applicability]
[0057] The CO methanation catalyst and the production method of the CO methanation catalyst of the present invention can reduce pressure loss and provide strong catalyst particles that do not affect subsequent stages. Therefore, the catalyst can be applied to large-scale plants that efficiently convert carbon monoxide contained in hydrogen-containing gas derived from fossil fuels and biomass into methane in a large amount. Furthermore, by applying the method for reducing carbon monoxide of the present invention to the reforming of fuel gas in a polymer electrolyte fuel cell, it is possible to reduce poisoning of the platinum catalyst contained in the cell electrodes and extend the life of the fuel cell.
Claims
1. A carbon monoxide methanation catalyst comprising ruthenium supported on spherical porous silica having a particle size of 1.0 mm or more and having a thin film or island-like titanium oxide on its surface.
2. 2. The carbon monoxide methanation catalyst according to claim 1, wherein the titanium oxide has a cyclic structure in which two or more titanium atoms are alternately bonded to oxygen atoms.
3. The carbon monoxide methanation catalyst according to claim 1 or 2, wherein the spherical porous silica has an average pore diameter of more than 10 nm.
4. The specific surface area of the spherical porous silica is 200 m 2 The carbon monoxide methanation catalyst according to claim 1 or 2, wherein the MnO2 content is 1 / g or less.
5. Adding a water-soluble titanium complex to spherical porous silica having a particle size of 1.0 mm or more; forming a thin film or islands of titanium oxide on the surface of the spherical porous silica by decomposition of the titanium complex; Supporting ruthenium on the spherical porous silica. A method for producing a carbon monoxide methanation catalyst.
6. 6. The method for producing a carbon monoxide methanation catalyst according to claim 5, wherein the water-soluble titanium complex is titanium ammonium peroxocitrate or a derivative thereof.
7. The method for producing a carbon monoxide methanation catalyst according to claim 5 or 6, wherein the titanium oxide has a cyclic structure in which two or more titanium atoms are alternately bonded to oxygen atoms.
8. and supporting ruthenium on the spherical porous silica using a hexaammineruthenium complex as a ruthenium precursor. A method for producing the carbon monoxide methanation catalyst according to claim 5 or 6.
9. A method for reducing carbon monoxide contained in a hydrogen-containing gas by converting carbon monoxide into methane using the carbon monoxide methanation catalyst according to claim 1 or 2.
Citation Information
Patent Citations
Co removal catalyst system and method for selective removal of co
JP2005067917A
Inorganic complex containing titanium oxide, and method for producing propylene oxide by using the complex as catalyst
JP2005193226A
Carbon monoxide methanation catalyst
JP2012250143A